Efektivitas Pembelajaran Tahfidz Al-Qur'an di Pondok Pesantren Al-Falah Balo Gesikan - Lovenida, Kuni Barorotul; Mustajab, Mustajab (IAINU Kebumen, 2026)
The background of this research is to see the importance of effective learning of Al-Qur'an tahfidz in order to improve the quality of memorizers both in terms of reading and the fluency of their memorization. The purpose of this research is to find out the tahfidz Al-Qur'an learning activities, the effectiveness of tahfidz Al-Qur'an learning, and the obstacles experienced during the learning process and their solutions. The research method used is descriptive qualitative research method using data analysis model of Milles and Huberman. The results of this study are (1) Learning tahfidz Al-Qur'an at the Al-Falah Balo boarding school is divided into two levels, namely: the bin Nadzri level and the bil Hifdzi level. The learning method used is the sorogan method. The learning activities are grouped into three, namely daily, weekly and monthly activities. (2) The learning of tahfidz Al-Qur'an at the Al-Falah Balo Islamic boarding school has been effective, marked by the achievement of predetermined learning indicators, namely: reading the Qur'an with tartil and mujawad, memorization must be smooth, and can be memorized. . (3) Obstacles that are often experienced during learning such as: drowsiness, laziness, lack of time sharing, illness, and the opposite sex. Solutions that can be done are: setting time for rest, reciting the Koran, and doing other activities, as well as reducing interaction with the opposite sex.